Complex IIa formation and ABC transporters determine sensitivity of OSCC to Smac mimetics - Yuhan Wang; Zijian Liu; Qian Si; Wanqiu Lu; Yuxian Song; Wanyong Jin; Xihu Yang; Zihui Li; Xinyang Hu; Liang Ding; Yue Jing; Pei Weng; et al. (Cell Death and Disease)
Abstract Small molecule inhibitors of apoptosis proteins (IAPs) antagonists, known as Smac mimetics (SMs), activate non-canonical NF-κB and sensitize cancer cells to TNF-induced cell death. SMs are currently in phase III clinical trials for head and neck squamous cell carcinoma (HNSCC) after promising phase II trials. To explore the utility of SMs in oral squamous cell carcinoma (OSCC), we tested nine human OSCC cell lines and correlated SM sensitivity with both IAP mutation and expression levels. cIAP1 protein expression was shown to be higher in OSCC and a predictor of poor prognosis. However, our in vitro and in vivo testing demonstrated differential sensitivity to SMs, which did not correlate with cIAP1 and cIAP2 expression in these OSCC cell lines. Exogenous TNF failed to effectively increase the sensitivity of SM-resistant OSCC cells to SM-induced cell death. SM resistance was associated with a deficiency in Complex IIa formation, but activation of non-canonical NF-κB was not a determinant of SM efficacy. Finally, metabolic analysis revealed that the ABC transporter pathway was activated in SM-resistant OSSC cells, and SMs combined with ABC transporter inhibitors improved cell death sensitivity to overcome SM resistance. These studies highlight the therapeutic potential of SMs in OSCC and support patient stratification to improve efficacy with the addition of adjuvant therapy.